Various Types of Neuroleukemia with Optic Nerve Involvement - E. E. Grishina; A. A. Ryabtseva; O. M. Andryukhina; A. A. Kovrizhkina (Oftalʹmologiâ, 2020)
Neuroleukemia is a severe complication of hemoblastosises characterized by infiltration of blast cells of the meninges, the substance of the brain, cranial and peripheral nerves.The purpose. To analyze the clinical manifestations of leukemia with optic nerve damage in leukemia and malignant lymphomas.Patients and Methods. From January 2016 to January 2020, one center-based non-randomized prospective study was conducted on patients with leukemia and non-Hodgkin’s lymphomas who were treated in the hematology department of MONIKI and made complaints about reduced vision. 26 patients were examined, 4 of them were diagnosed neuroleukosis with leukemic infiltration of the optic nerves: three women aged 41, 44, 46 years and a man aged 50 years.Results. All patients had one common ophthalmological symptom — decreased visual acuity. Complaints of reduced vision in one patient appeared at the onset of the disease, in other patients-during a relapse. The picture of the eye’s fundus in all patients was identical: the optic disk had blurred borders, and elevated above the retina. In the first days, the vascular funnel was viewed, then closed by infiltration. A dense white infiltrate of the peripapillary retina spread over the entire macular area. The retinal veins were sharply dilated of uneven caliber. Along the course of the vessels, there were a large number of different sizes and shapes of hemorrhages. Various types of neuroleukemia with lesion of the optic nerve were described: a combination of focal lesions of the brain and the optic nerve, isolated damage to the optic nerve with blast cytosis in the cerebrospinal fluid (CSF), isolated damage to the intraocular part of the optic nerve without changing the cerebrospinal fluid. In three patients the diagnosis of neuroleukemia exhibited on the basis of changes according to magnetic resonance imaging (MRI) and/or the number of blast cells in punctate liquorologic research. In the fourth patient, in the absence of changes in the liquor and MRI, the diagnosis of leukemic infiltration of the optic nerve was confirmed by data from a cytological examination of a punctate from the peripapillary retina. After the beginning of antitumor treatment, the significant improvement visual acuity and decrease in leukemic infiltrate of the optic disc and retina of the affected eye was noted in all patients.Discussion. Damage of the optic nerve can develop both at the onset of the disease, and relapses of leukemia or aggressive non-Hodgkin’s lymphomas. Leukemic infiltration evolves in all parts of the optic nerve, but more often affects its intraocular portion. The damage to the intraocular part is characterized by the presence of a dense infiltrate both in the area of the papilla and the peripapillary retina.Conclusion. Leukemic infiltration of the optic nerve is manifested by a significant decrease in visual acuity. Careful attention to complaints of reduced vision in patients with leukemia can help to recognize the development of the disease’s debut or its progression. Timely antitumor treatment leads to an improvement in visual acuity and, consequently, an improvement in the quality of life of patients.